AN ACCELERATION OF FPGA-BASED RAY TRACER - Raisa Malcheva; Mohammad Yunis (European Scientific Journal, ESJ, 2014)
The Hardware implementations of the Ray Tracing algorithm are analyzed. A possibility of not all pixels tracing is discussed. The structure of Modified FPGA-based system is proposed. A productivity of Modified Ray Tracing algorithm is researched.